The Role of Profitability in the Influence of E-Commerce Implementation and Financial Accounting Standards on Enhancing the Competitiveness of Micro, Small, and Medium Enterprises (MSMEs) - Sri Ayem; Rifki Darmawan (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study aims to analyze the influence of e-commerce implementation and the Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM) on enhancing MSMEs’ competitiveness, with profitability as a moderating variable. In the face of the digital era and increasing market competition, MSMEs are required to adapt by utilizing information technology and improving financial governance. The research method used is quantitative, employing a survey approach involving a number of MSME actors. The results show that both e-commerce implementation and SAK EMKM have a positive and significant effect on improving MSME competitiveness. Furthermore, the profitability variable is proven to strengthen the relationship between e-commerce and competitiveness, but does not enhance the relationship between SAK EMKM and competitiveness. These findings align with Contingency Theory, which states that the effectiveness of a strategy depends on its alignment with an organization’s internal and situational conditions. In the context of MSMEs, the success of digital and accounting strategies is highly influenced by technological readiness, leadership quality, and the financial condition of the business. This study provides practical implications for MSME actors, the government, and other stakeholders in formulating business development strategies amidst digital economic transformation.